Evaluation of the effectiveness of Washington State’s digital COVID-19 exposure notification system over one pandemic year - Elder, Adam S.; Arrouzet, Cory J.; Miljacic, Ljubomir; Karras, Bryant T.; Higgins, Amanda; West, Laura M.; Lorigan, Daniel; Revere, Debra; Polissar, Nayak; Segal, Courtney D.; Lober, William B.; Baseman, Janet G. (Frontiers in Public Health, 2024)
Introduction Digital exposure notifications are a novel public health intervention used during the COVID-19 pandemic to alert users of possible COVID-19 exposure. We seek to quantify the effectiveness of Washington State’s digital exposure notification system, WA Notify, as measured by the number of COVID-19 cases averted during a 1-year period. Methods While maintaining individuals’ privacy, WA Notify collected data that could be used to evaluate the system’s effectiveness. This article uses these and other data and builds on a previous model to estimate the number of cases averted by WA Notify. Novel estimates of some model parameters are possible because of improvements in the quality and breadth of data reported by WA Notify. Results We estimate that WA Notify averted 64,000 (sensitivity analysis: 35,000–92,000) COVID-19 cases in Washington State during the study period from 1 March 2021 to 28 February 2022. During this period, there were an estimated 1,089,000 exposure notifications generated and 155,000 cases reported to WA Notify. During the last 78 days of the study period, the median estimated number of daily active users was 1,740,000. Discussion We believe WA Notify reduced the impact of the COVID-19 pandemic in Washington State and that similar systems could reduce the impact of future communicable disease outbreaks.